Evolving Perspectives on Innate Immune Mechanisms of IPF - Ishikawa, Genta; Liu, Angela; Herzog, Erica L. (Frontiers in Molecular Biosciences, 2021)
While epithelial-fibroblast interactions are viewed as the primary drivers of Idiopathic Pulmonary Fibrosis (IPF), evidence gleaned from animal modeling and human studies implicates innate immunity as well. To provide perspective on this topic, this review synthesizes the available data regarding the complex role of innate immunity in IPF. The role of substances present in the fibrotic microenvironment including pathogen associated molecular patterns (PAMPs) derived from invading or commensal microbes, and danger associated molecular patterns (DAMPs) derived from injured cells and tissues will be discussed along with the proposed contribution of innate immune populations such as macrophages, neutrophils, fibrocytes, myeloid suppressor cells, and innate lymphoid cells. Each component will be considered in the context of its relationship to environmental and genetic factors, disease outcomes, and potential therapies. We conclude with discussion of unanswered questions and opportunities for future study in this area.